2021
DOI: 10.1111/clr.13716
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective long‐term clinical evaluation of implant‐prosthetic rehabilitations after head and neck cancer therapy

Abstract: Objective To assess clinical and patient‐reported outcomes of implant‐prosthetic rehabilitations in patients with a history of head–neck cancer (HNC), treated with tumor resection without (TR) or with adjuvant radiotherapy (TR/RT). A healthy cohort rehabilitated with the same reconstructive protocols served as control group (C). Materials and Methods A total of 28 women and 29 men were considered in the present retrospective study. Participants received 322 implants, finally supporting 79 prosthetic reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 57 publications
3
29
1
Order By: Relevance
“…Furthermore, Ettl et al (2020) concluded that radiation with a dose of over 60 Gray negatively influenced implant success ( p = .025). Contrary to that, other studies found only a minor influence of radiotherapy on the outcome of dental implantation (Alberga et al, 2020; Dholam et al, 2013; Laverty et al, 2019; Moore et al, 2019; Patel et al, 2020; Woods et al, 2019) or even resulted in comparable survival rates for implants placed in the two above‐mentioned groups (Ch'ng et al, 2016; Gander et al, 2014; Pieralli et al, 2021). All irradiated patients included into the studies by Doll et al (2015) and Hessling et al (2015) were treated with radiochemotherapy.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Furthermore, Ettl et al (2020) concluded that radiation with a dose of over 60 Gray negatively influenced implant success ( p = .025). Contrary to that, other studies found only a minor influence of radiotherapy on the outcome of dental implantation (Alberga et al, 2020; Dholam et al, 2013; Laverty et al, 2019; Moore et al, 2019; Patel et al, 2020; Woods et al, 2019) or even resulted in comparable survival rates for implants placed in the two above‐mentioned groups (Ch'ng et al, 2016; Gander et al, 2014; Pieralli et al, 2021). All irradiated patients included into the studies by Doll et al (2015) and Hessling et al (2015) were treated with radiochemotherapy.…”
Section: Discussionmentioning
confidence: 93%
“…The importance of the oral rehabilitation of patients treated for head and neck cancer is beyond question, especially in view of the improvement of health‐related quality of life (AWMF, 2015; Petrovic et al, 2019; Pieralli et al, 2021; Woods et al, 2019). Implant therapy plays an important role in the reconstruction of esthetical and functional defects and in the restoring of the masticatory function, particularly through better retention of the prosthetic superstructure (Buurman et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis by Chambrone et al showed a higher risk for implant failure in radiated patients compared to non-irradiated patients [ 18 ]. However, a recent study showed similar survival rates in both, patients who received radiation therapy and those who did not receive radiation therapy during their oncological treatment [ 19 ]. It should be mentioned that this study had very strict eligibility criteria and therefore other variables influencing long-term implant survival were excluded.…”
Section: Introductionmentioning
confidence: 99%